(untitled) (Revista Latino-Americana de Enfermagem, 2003)
The authors present the experience of teaching pediatric nursing at the Universidade Federal de Mato Grosso do Sul (UFMS), Brazil. They carried out a qualitative analysis of the learners' evaluation for the year 2000, from which two categories emerged: "being a different experience" and "changing the way the learners see the child and the family". They conclude that choosing the person-centered teaching approach has been of fundamental importance for the learner to achieve personal and professional autonomy.